2005
DOI: 10.1097/01.tp.0000183962.64777.da
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Ablation Enhances Lymphoid Recovery Following Autologous Hematopoietic Stem Cell Transplantation

Abstract: These data suggest that sex steroid ablation significantly enhances lymphopoiesis following auto-HSCT providing a new strategy for posttransplant immune reconstitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 81 publications
1
56
0
Order By: Relevance
“…Since immunity can be restored faster following chemotherapy and hemopoietic stem cell transplantation, using reversible sex steroid blockade (52,(75)(76)(77)(78), hemopoietic stem cell transplantation may be rendered safe enough to reinstate tolerance in some autoimmunity patients given a similar though less myeloablative regime. However, any underlying stromal defects must be considered, as their effects could be magnified following thymic hypertrophy, increasing the risk of relapse, particularly if stromal cells are incapable of expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Since immunity can be restored faster following chemotherapy and hemopoietic stem cell transplantation, using reversible sex steroid blockade (52,(75)(76)(77)(78), hemopoietic stem cell transplantation may be rendered safe enough to reinstate tolerance in some autoimmunity patients given a similar though less myeloablative regime. However, any underlying stromal defects must be considered, as their effects could be magnified following thymic hypertrophy, increasing the risk of relapse, particularly if stromal cells are incapable of expansion.…”
Section: Discussionmentioning
confidence: 99%
“…B cell development is also negatively regulated by sex steroids and again removal of sex steroids enhances B cell development and reverses age-related decreases in B cell production [20;21]. Sex steroid ablation results in a significant increase in B and T cell reconstitution after both autologous [22] and allogeneic [23] HSCT and in humans who underwent reversible chemical castration using an LHRH agonist [24].…”
Section: Hormones Growths Factors and Cytokinesmentioning
confidence: 99%
“…Interestingly, sex-associated hormones, including androgens and estrogen, have been directly implicated in regulating hematopoietic cell function. [2][3][4] During the course of our functional analyses of HSCs using the recently developed NOD/SCID/ IL-2Rg c -null (NSG) mice, 5 we observed that the recipient sex plays a critical role in the engraftment and proliferation of human HSCs. Specifically, female NSG mice are far superior to their male counterparts in engrafting and detection of single human HSCs.…”
Section: Introductionmentioning
confidence: 99%